2017
DOI: 10.1016/j.thromres.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles in acute coronary syndrome

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
2
6
1
Order By: Relevance
“…Interestingly, STEMI patients had elevated absolute levels of total Annexin V + EV compared to VA-ECMO patients. This is in line with previous reports of elevated EV concentrations in STEMI patients compared to other patients with vascular inflammation, e.g., NSTEMI patients, patients recovering from STEMI and patients with stable angina (22,(39)(40)(41)(42). Elevated EV levels most likely reflect the release of MV during the thrombotic process, from activated cells and from the ischemic myocardium after reperfusion (17,43).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, STEMI patients had elevated absolute levels of total Annexin V + EV compared to VA-ECMO patients. This is in line with previous reports of elevated EV concentrations in STEMI patients compared to other patients with vascular inflammation, e.g., NSTEMI patients, patients recovering from STEMI and patients with stable angina (22,(39)(40)(41)(42). Elevated EV levels most likely reflect the release of MV during the thrombotic process, from activated cells and from the ischemic myocardium after reperfusion (17,43).…”
Section: Discussionsupporting
confidence: 91%
“…Levels of leukocyte (CD45 + ) EV did not differ significantly in VA-ECMO and STEMI patients. This is most likely due to the fact that increased levels of leukocyte EV have been reported in both ECMO (10,38) and STEMI patients (42). Interestingly, the level of leukocyte EV was increased in nonsurvivors of VA-ECMO therapy indicating an association with outcome.…”
Section: Discussionmentioning
confidence: 92%
“…Emerging evidence indicates that EVs released from activated cells contain procoagulant and proinflammatory molecules that may contribute to thrombus formation and endothelial dysfunction . Several clinical studies have shown a correlation between circulating EVs levels and clinical outcomes, markers of myocardial damage, inflammation, and evidences of microvascular dysfunction . Likewise, circulating EVs are shown to be increased in patients with ACS compared with healthy and stable coronary artery disease (SCAD) individuals pointing toward the importance of EVs as novel prognostic biomarkers to predict the outcome of ACS patients .…”
Section: Evs Proteomics In Cardiovascular Diseasementioning
confidence: 99%
“…These are prothrombotic and proinflammatory 10,11 . The levels of PS-exposing EVs are increased in many cardiovascular and metabolic disorders [12][13][14][15][16][17] , and platelets are the major source of circulating PS-exposing EVs 11,18 . The pathological role of PSexposing EVs, and their elevation in a range of diseases, makes them an attractive therapeutic target.…”
Section: Introductionmentioning
confidence: 99%